Exploring Islamic Character Values in Nussa The Movie: Relevance and Implementation in Islamic Education - M. Ferry Irawan; Nikentari Rizky; Alia Latifah (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This research delves into depicting Islamic character values in 'Nussa The Movie,' examining its relevance and application in Islamic education. Employing a qualitative methodology with descriptive content analysis, the study scrutinizes the movie's narrative, dialogues, and visual elements. Seven key Islamic character values identified include good role modeling, wisdom, generosity, patience, honesty, justice, and sincerity. The findings suggest that 'Nussa The Movie' transcends mere entertainment, emerging as a potent tool for imparting Islamic character education to children. These values are intricately interwoven with the movie’s narrative, offering viewers examples of character traits aligned with Islamic teachings. Despite its educational potential, the study acknowledges limitations and encourages further research on long-term impacts and cultural variations in character education through animated media. This research emphasizes the importance of this film as a resource for educators and parents in instilling Islamic values, thus contributing to a broader discussion on the integration of entertainment and education in character development.